Development of digital-based children's story books to improve early reading literacy in early childhood - Supenny Supenny; Delfi Eliza; Nenny Mahyuddin; Setiyo Utoyo (Indonesian Institute For Counseling, Education and Therapy, 2026)
Early reading literacy skills of early childhood children at Az-Zahra Islamic School Kindergarten have not developed optimally due to reliance on conventional media that is less interactive and varied. This study aims to: (1) measure the validity level of the developed digital-based children's storybook; (2) determine the level of practicality of its use by PAUD teachers; and (3) evaluate its effectiveness in improving early reading literacy of children aged 5–6 years. The method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects were 60 children aged 5–6 years from three PAUD institutions, with 19 children as the main effectiveness test subjects. The product was developed using the Canva and Heyzine Flipbook platforms, containing audio narration, animation, and interactive illustrations integrated with the character value of tolerance. Validation was carried out by two expert validators from Padang State University. The validation results showed an average of 92% (media experts: 90%; instrument experts: 94%), categorized as Very Valid. The practicality test obtained a score of 95% (Very Practical). Effectiveness testing showed an increase from 82% in the initial trial to 91% in full implementation, with 84% of children (16 of 19) achieving the Very Well Developed (BSB) category. These findings confirm that the developed digital storybook is valid, practical, and effective in supporting early childhood reading literacy, as well as relevant to the implementation of the Independent Curriculum.